O papel dos missionários Xaverianos na educação masculina do colégio São Francisco Xavier, em Abaetetuba – Pará (1966-1975) - FERREIRA, Evem Neuily Barbosa (2019)
This research proposes to reconstruct a historiography of the education of the College of St. Francis Xavier (1966-1975), founded and maintained by the Diocese of Abaetetuba - Pará. It also aims to understand its influence in the life of the children who studied in the establishment in that period. In general, this study discusses how the Xaverian Missionaries contributed to the social and educational development of the Baetetubense municipality, thoroughly exhuming the history and functioning of one of its greatest achievements for local society: the implementation of the São Francisco Xavier College in 1966, exclusively male, as a way to meet the educational needs of the region at the time. It was also aimed to identify the pedagogical proposal of the institution; verify the access of students to school; class and series entrenchment and check the disciplines of the school curriculum. Methodologically, the research is based on the theoretical assumptions of the New Cultural History, because it allows us to carry out the cross-linking of sources. Thus, we used documentary and bibliographical techniques to perform data collection in order to achieve more expressive results. For documentary analysis, the documents available in the CSFX collection were explored, such as: reports from directors, decrees, school curriculum, among others. For the bibliographic analysis, the works of Machado (1986), Rocha (2010) and Araújo (2012) were used. The analysis confirms that the Catholic educational action of the Xaverian Missionaries sought, together with their educational assumptions, to deepen the learning of the way of being, trying to maintain control over male students, through the practice of civism, Christian morality and good manners , in order to fulfill his goals of formation of the "perfect man".